Strategic communication and behavioral coupling in asymmetric joint action - Vesper, Cordula (Exp Brain Res, 2014)
How is coordination achieved in asymmetric joint actions where co-actors have unequal access to task information? Pairs of participants performed a non-verbal tapping task with the goal of synchronizing taps to different targets. We tested whether ‘Leaders’ knowing the target locations would support ‘Followers’ without this information. Experiment 1 showed that Leaders tapped with higher amplitude that also scaled with specific target distance, thereby emphasizing differences between correct targets and possible alternatives. This strategic communication only occurred when Leaders’ movements were fully visible, but not when they were partially occluded. Full visual information between co-actors also resulted in higher and more stable behavioral coordination than partial vision. Experiment 2 showed that Leaders’ amplitude adaptation facilitated target prediction by independent Observers. We conclude that fully understanding joint action coordination requires both representational (i.e., strategic adaptation) and dynamical systems (i.e., behavioral coupling) accounts.